Gates/Buffet versus Bezos/Musk : donate or invest? - Osland, Asbjorn (London : SAGE Publications: SAGE Business Cases Originals, 2020)
In contrasting approaches, Elon Musk and Jeff Bezos have chosen to use some of their wealth to build rocketry businesses, while Bill and Melinda Gates and Warren Buffett have chosen philanthropy. A question The Economist (2011) posed after analyzing IBM versus the Carnegie Corporation in recognition of their respective 100th anniversaries in 2011 is still relevant: "Has the multinational business or universal philanthropy done more for society?" Paraphrased for this context, it reads, "Is the Gates-Buffett approach to philanthropy a better use of money than rocketry as envisioned by Bezos-Musk?" This is the question students are asked to ponder.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; Gates, Bill, -- 1955-; electronic books; Buffett, Warren; Musk, Elon; Bezos, Jeffrey; Social responsibility of business -- Case studies; Businessmen -- United States -- Biography; Philanthropists -- Untied States -- Biography